Peran Komitmen Afektif, Kecerdasan Emosional dan Dukungan Organisasional Terhadap Organizational Citizenship Behavior Studi Pada Dinas Perindustrian dan Perdagangan DI Yogyakarta - Fala, Handita; Prayekti, Prayekti; Kirana, Kusuma Candra (Jurnal Ilmiah Manajemen Kesatuan, 2021)
This study aims to determine (1) the influence of Affective Commitment to OCB, (2) the influence of Emotional Intelligence on OCB, (3) the influence of Organizational Support on OCB, and (4) the influence jointly of Affective Commitment, Emotional Intelligence and Organizational Support to OCB. The type of research used is quantitative research. The population in this study is a permanent employee of the Office of Industry and Trade of the Special Region of Yogyakarta which amounts to 68 people. The sample of this study because less than 100 then 68 permanent employees were involved all. Data collection method using questionnaire using Judgement Sampling technique or often called Purposive Sampling. This study used data quality test, classic assumption test (normality test, heterocysticity test, and multicollinierity test), multiple linear regression analysis, and hypothesis test. The results of this study showed that Affective Commitment Variables have no effect on OCB Variables. Emotional Intelligence Variables have a positive and significant effect on OCB. Organizational Support Variables have a positive and significant effect on OCB. Variable Affective Commitment, Emotional Intelligence and Organizational Support together or simultaneously affect OCB.